The 50 worst terrorist attacks - Mickolus, Edward F. 1950-; Simmons, Susan L. (Praeger, 2014)
"In the last 50 years, terrorists have committed hundreds of horrific acts of violence to further their causes. This accessible, single-volume text covers the most significant terrorist acts across contemporary history worldwide"..